Acoustofluidic trapping device for high-NA multi-angle imaging - Løvmo, Mia Kvåle; Moser, Simon; Thalhammer-Thurner, Gregor; Ritsch-Marte, Monika (Frontiers in Physics, 2022)
In the life sciences there has been growing awareness that the traditional 2D cell culture model has its limitations to advance our understanding of the mechanisms that underlie cell behaviour, as the behaviour and response of cells depends on the 3D micro-environment. Studying models such as suspended cell clusters and organoids is a step towards closing the gap between in vitro and in vivo studies. The fact that sample confinement and contact to surfaces has an impact on cells, creates a need for contact-less tools for inspection of live biological samples. Recently we have developed an acoustofluidic chip to trap and manipulate sub-millimeter sized biological samples, and here we demonstrate that this device can be adapted to support high resolution imaging as well as illumination scanning for multi-view image acquisition. Coupling acoustic bulk waves into a microfluidic chip, the sample is levitated by an optically transparent transducer in the vertical direction. Two orthogonal side-transducers give additional control on the sample. By tuning the relative strength of the three transducers, and thus inducing an acoustic torque, we can transiently rotate the sample into various orientations for image acquisition. Under different operating conditions, exciting other modes, we can also induce sustained rotation of samples by means of other torque contributions, also around axes perpendicular to the imaging axis, which is important to avoid 'missing cone' artifacts in the tomographic reconstruction of the sample. We will discuss the modifications of our previously established device that were necessary to comply with the requirements for high-NA imaging and high-NA illumination. We provide a characterization of the performance and show examples of rotation and reorientation of biological samples, such as large pollen grains and cancer spheroids.